Numerical Analysis of Lateral- Torsional Buckling in Tapered Web I-Steel Beams - Pratiwi, Naomi; Wijaya, Paulus Karta; Hardianto, Lintang Ayu Dewintasari (Jurnal Teknik Sipil, 2026)
The phenomenon of lateral–torsional buckling (LTB) in nonprismatic web-tapered steel beams is not yet explicitly covered in SNI 1729:2020, which was developed based on prismatic sections. This regulatory gap creates uncertainties in determining the capacity of beams with varying cross-sections. This study investigates the LTB behavior of web-tapered beams through nonlinear finite element analysis, accounting for geometric imperfections and residual stresses. A parametric analysis was conducted by varying the taper ratio, unbraced length, and load application points (at the shear center and top flange) for both uniformly distributed and concentrated loads. The results indicate that the combined effects of geometric imperfections and residual stresses reduce the critical moment by approximately 23% on average relative to the critical moment formulation. Furthermore, increasing taper ratio, unbraced length, and the destabilizing load configurations further decrease the critical moment capacity. Based on calibration against the numerical dataset, a set of geometric and loading correction factors is proposed to modify the critical moment formulation in SNI 1729:2020. The proposed model demonstrates good agreement with the numerical results, with an average prediction error of 3.99%, a maximum deviation of 13.96%, and a coefficient of determination (R²) of 0.92. The resulting equation provides a practical and rational design-oriented approach for secondary steel beam applications without requiring full nonlinear finite element analysis.